Control strategies for charging and discharging policies of rechargeable batteries - Anthoni (2012)
From lithium based battery chemistries and technologies, control management techniques must be used to avoid high voltage potentials in order to eliminate or reduce the amount of electrolyte decomposition and also prevent lithium batteries from being discharged to excessively low potentials to avoid the copper current collector dissolving in the electrolyte. The dissolved copper will be plated onto the anode’s graphite particles on subsequent recharges of the cell, which will inhibit the utilization of the active material and reduce the cell’s performance and life. In addition, excessive operating currents can cause permanent damage to a lithium-ion battery. Excessive discharge currents may not permanently damage cells, but polarization will occur. Polarization, due to the inability to move lithium ions through the electrolyte and in and out of the active materials, will greatly reduce the cell’s performance. In summary, without suitable strategies to control charging and discharging of cells, the operation of battery pack cannot be maintained at their optimal working conditions and this will result in the wastage of energy and reduction of lifespan or even damage of batteries.